Bases conceptuales de la educación intercultural. De la diversidad cultural a la cultura de la diversidad - Juan José Leiva Olivencia (FahrenHouse, 2013)
Our land has been in recent decades as a country of emigrants to become the host country of immigrants from various places, ethnicities, customs, languages and religions. For his part, and focusing on the educational context, it is clear the existence of multicultural classrooms and multicultural phenomenon understood as the plurality of students from diverse educational environments in common. However, some years ago in education, many authors use the terms of intercultural school and intercultural education as a way of taking the educational model based on enriching interdependence of different cultural values in educational practice, while multiculturalism would be an expression describing the situation of coexistence of various cultures in the same educational space. Therefore, it is essential to outline the key characteristics of intercultural education, addressing key elements that define it, that is, diversity, culture, citizenship and identity, to build an intercultural education based on the recognition of cultural diversity, is capable creating a culture of diversity, a benchmark for inclusive teaching about educational institutions that want to be inclusive and intercultural.  Received: 17/09/2012 / Accepted: 29/10/2012 How to reference this article Leiva Olivencia, J. J. (2013). Bases conceptuales de la educación intercultural. De la diversidad cultural a la cultura de la diversidad. Foro de Educación, 11(15), pp. 169-197. doi: http://dx.doi.org/10.14516/fde.2013.011.015.008